Prospective Evaluation of Cardiopulmonary Resuscitation Performed in Dogs and Cats According to the RECOVER Guidelines. Part 2: Patient Outcomes and CPR Practice Since Guideline Implementation - Hoehne, Sabrina N.; Hopper, Kate; Epstein, Steven E. (Frontiers in Veterinary Science, 2019)
Cardiopulmonary resuscitation (CPR) outcomes have not been prospectively described since implementation of the RECOVER guidelines. This study aimed to prospectively describe CPR outcomes and document arrest variables in dogs and cats at a U.S. veterinary teaching hospital since implementation of the RECOVER guidelines using the 2016 Utstein-style reporting guidelines. One-hundred and seventy-two dogs and 47 cats that experienced cardiopulmonary arrest (CPA) underwent CPR following implementation of the RECOVER guidelines and were prospectively included. Supervising clinicians completed a data form for CPR events immediately following completion of CPR from December 2013 to June 2018. Seventy-five (44%) dogs and 26 (55%) cats attained return of spontaneous circulation (ROSC), 45 dogs (26%) and 16 cats (34%) had ROSC > 20minutes, 13 dogs (8%) and 10 cats (21%) were alive 24h after CPR, and 12 dogs (7%) and 9 cats (19%) survived to hospital discharge. The most common cause of death in animals with ROSC > 20 minutes was euthanasia. Patient outcomes were not significantly different since publication of the RECOVER guidelines except for a higher feline survival to hospital discharge rate. Dogs (p=0.02) but not cats with initial shockable rhythms had increased rates of ROSC while the development of a shockable rhythm during CPR efforts was not associated with ROSC (p=0.30). In closed chest CPR an end-tidal CO2 value of >16.5 mmHg was associated with a 75% sensitivity and 64% specificity for achieving ROSC. Since publication of the RECOVER guidelines, CPR practice did not clinically significantly change at our institution and no improvement of already high ROSC rates was noted. The percentage of cats surviving to hospital discharge was higher than previously reported and the reason for this improvement is not evident with these results. Euthanasia remains a major confounding factor in assessing intermediate and long-term CPR outcomes in dogs and cats.